(64)Cu-NO2A-RGD-Glu-6-Ahx-BBN(7-14)NH(2): a heterodimeric targeting vector for positron emission tomography imaging of prostate cancer - Jackson, Andrew B. (2012)
INTRODUCTION: The present study describes the design and development of a new heterodimeric RGD-bombesin (BBN) agonist peptide ligand for dual receptor targeting of the form (64)Cu-NO2A-RGD-Glu-6-Ahx-BBN(7-14)NH(2) in which Cu-64=a positron emitting radiometal; NO2A=1,4,7-triazacyclononane-1,4-diacetic acid; Glu=glutamic acid; 6-Ahx=6-aminohexanoic acid; RGD=the amino acid sequence [Arg-Gly-Asp], a nonregulatory peptide that has been used extensively to target α(v)β(3) receptors up-regulated on tumor cells and neovasculature; and BBN(7-14)NH(2)=Gln-Trp-Ala-Val-Gly-His-Leu-Met-NH(2), an agonist analogue of bombesin peptide for specific targeting of the gastrin-releasing peptide receptor (GRPr). METHODS: RGD-Glu-6-Ahx-BBN(7-14)NH(2) was manually coupled with NOTA (1,4,7-triazacyclononane-1,4,7-triacetic acid), and the resulting conjugate was labeled with (64)Cu to yield (64)Cu-NO2A-RGD-Glu-6-Ahx-BBN(7-14)NH(2). Purification was achieved via reversed-phase high-performance liquid chromatography and characterization confirmed by electrospray ionization–mass spectrometry. RESULTS: Competitive displacement binding assays displayed single-digit nanomolar IC(50) values showing very high binding affinities toward the GRPr for the new heterodimeric peptide analogues. In vivo biodistribution studies showed high uptake and retention of tumor-associated radioactivity in PC-3 tumor-bearing rodent models with little accumulation and retention in nontarget tissues. The radiolabeled conjugate also exhibited rapid urinary excretion and high tumor-to-background ratios. Micro-positron emission tomography (microPET) molecular imaging investigations produced high-quality, high-contrast images in PC-3 tumor-bearing mice 15 h postinjection. CONCLUSIONS: Based on microPET imaging experiments that show high-quality, high-contrast images with virtually no residual gastrointestinal radioactivity, this new heterodimeric RGD-BBN conjugate can be considered as a promising PET tracer candidate for the diagnosis of GRPr-positive tumors in human patients.